Evaluation of friction coefficient of an auto-body steel sheet - Trzepieciński, Tomasz; Kubit, Andrzej; Fejkiel, Romuald; Bochnowski, Wojciech (Advances in Mechanical and Materials Engineering, 2016)
In this paper the results of strip drawing tests aimed to determine the friction coefficient in sheet metal forming operations are presented. The tests were conducted using a specially designed tribological simulator. The deep drawing quality steel sheet used in the automotive industry was tested. The relationship that shows the effect of sheet normal load, tool surface roughness, lubrication conditions and sample orientation according the rolling direction of the sheet on the value of friction coefficient are presented and discussed. The Scanning Electron Microscope (SEM) micrographs of sheet surfaces after the friction test allowed us to identify the mechanisms that occur at the contact of two bodies with rough surfaces. The results of the tests indicate that the relationship between friction force and normal force is nonlinear. Thus, the value of the friction coefficient is changed with the change of the load value.